Profitability ratio analysis to assess the financial performance - Rahmah Fadillah, Iin; Nadiyah, Nadiyah; Rohmah, Lutfiyatul; Haryadi, Didit; Wahyudi, Wahyudi (Trigin Publisher, 2024)
Financial ratios become an illustration in consideration materials to explain the values in the financial statements. All aspects of the business sector are crucial in paying attention to financial management in banking, industry, manufacturing, and retail. This is because the financial sector applies financial principles in an institution to create optimal value to make decisions and appropriately manage resources owned by the company. This study uses data analysis based on financial statements by measuring, knowing, illustrating, and comparing charts in financial statements, especially the balance sheet and profit and loss. Ratio analysis uses a method of financial statement analysis that looks at a certain period of years and then compares financial statements with different years through sections of the financial statements. This study aims to develop a model for reviewing financial statements from financial performance. This research is expected to make theoretical contributions to the literature in this context, including in the context of financial and banking management.